2013
DOI: 10.1108/08858621311330236
|View full text |Cite
|
Sign up to set email alerts
|

How customer knowledge dissemination links to KAM

Abstract: Purpose -This study aims to identify the organizational antecedents of intra-organizational customer knowledge dissemination in the context of key account management (KAM). Design/methodology/approach -The data were collected from large industrial companies in Finland by means of a structured survey. Linear hierarchical regression analysis was used to test the hypotheses. Findings -The findings of the study show that esprit de corps among employees and the formalization of key account management facilitate cus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 74 publications
0
21
0
Order By: Relevance
“…The "outcomes" dimension exposes the consequences of the degree of knowledge management effectively achieved in a company's performance, innovation capability and product, and service quality (Lin, 2007). Salojärvi, Saarenketo, and Puumalainen (2013) follow this general framework for proposing the model for CKM. Other scholars recognize the existence of different influences on CKM activities, such as Human, Organizational, and Technological factors (Feher & Gabor, 2006;Ghobadi, 2015;Lin, 2007;Salojärvi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The "outcomes" dimension exposes the consequences of the degree of knowledge management effectively achieved in a company's performance, innovation capability and product, and service quality (Lin, 2007). Salojärvi, Saarenketo, and Puumalainen (2013) follow this general framework for proposing the model for CKM. Other scholars recognize the existence of different influences on CKM activities, such as Human, Organizational, and Technological factors (Feher & Gabor, 2006;Ghobadi, 2015;Lin, 2007;Salojärvi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Salojärvi, Saarenketo, and Puumalainen (2013) follow this general framework for proposing the model for CKM. Other scholars recognize the existence of different influences on CKM activities, such as Human, Organizational, and Technological factors (Feher & Gabor, 2006;Ghobadi, 2015;Lin, 2007;Salojärvi et al, 2013). Orlikowski (1992) proposed the theory to show the interaction among people, organization, and technology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…KAM enables a firm to devote special attention to its largest and most important customers, especially when such customers comprise a substantial part of its total sales (Salojärvi et al, 2013;Stevenson and Page, 1979;Storbacka, 2012;Weilbaker and Weeks, 1997). Since these accounts make significant purchases, or at least have the potential to do so, they represent great sales opportunities, but if they already purchase substantially, they also pose a great risk (Shapiro and Moriarty, 1982;Piercy and Lane, 2006).…”
Section: Kam Reviewmentioning
confidence: 99%
“…Another body of literature has emphasized the importance of input by the customer, henceforth referred to as the customer's knowledge as this study is performed in the context of collaborative customer-supplier relationships (Day, 2000;Campbell, 2003;Lin and Huang, 2013). Firms that proactively use this knowledge in order to foster and enhance long-term relationships can create a significant competitive advantage (Campbell, 2003;Jayachandran et al, 2005;Salojärvi et al, 2013). Indeed, several studies regarding the role of the customer in NPD have revealed the importance of the customer's knowledge in collaborative product development (Fang et al, 2008;Athaide and Klink, 2009;Fuchs and Schreier, 2011).…”
Section: Introductionmentioning
confidence: 99%